Multi-catalysis induced by pulsed discharge plasma coupled with graphene-Fe3O4 nanocomposites for efficient removal of ofloxacin in water: Mechanism, degradation pathway and potential toxicity. (February 2021) - Guo, He; Li, Zhen; Lin, Siying; Li, Dongsheng; Jiang, Nan; Wang, Huijuan; Han, Jiangang; Li, Jie
Abstract: Herein, degradation of ofloxacin (OFX) by pulsed discharge plasma (PDP) coupled with multi-catalysis using graphene-Fe3 O4 nanocomposites was inspected. The graphene-Fe3 O4 nanocomposites were prepared by hydrothermal synthesis, and their morphology, specific surface area, chemical bond structure and magnetic property were characterized systematically. Compared with sole Fe3 O4, the specific surface area of graphene-Fe3 O4 nanocomposites increased from 26.34 m 2 /g to 125.04 m 2 /g. The prepared graphene-Fe3 O4 nanocomposites had higher paramagnetism and the magnetic strength reached 66.05 emu/g, which was prone to separate from solution. Graphene-Fe3 O4 nanocomposites could further accelerate OFX degradation compared to sole Fe3 O4 . When graphene content was 18 wt%, graphene-Fe3 O4 nanocomposites exhibited the highest catalytic activity, and the removal efficiency of OFX enhanced from 65.0% (PDP alone) to 99.9%. 0.23 g/L dosage and acid solution were beneficial for OFX degradation. Higher stability of graphene-Fe3 O4 nanocomposites could be maintained although four times use. Graphene-Fe3 O4 nanocomposites could catalyze H2 O2 and O3 to produce more ·OH. The degradation products of OFX were identified by liquid chromatography mass spectrometry (LC-MS) and ion chromatography (IC). According to the identified products and discrete Fourier transform (DFT), the degradation pathway was inferred. Further toxicity assessment of products manifested that the toxicity of oral rat 50% lethal dose (LD50 ) and the developmental toxicity of OFX were reduced. Graphical abstract: Image 1 Highlights: PDP assisted with rGO-Fe3 O4 for ofloxacin degradation was inspected. Graphene-Fe3 O4 further improved removal efficiency of OFX compared to Fe3 O4 . Graphene-Fe3 O4 could catalyze H2 O2 and O3 to produce more ·OH. Degradation pathway was proposed according to intermediates and DFT analysis. The toxicity of OFX was alleviated by PDP coupled with graphene-Fe3 O4 .